Public participation in Local Agenda 21: A review of traditional and innovative tools - Julie Catherine Sors (Fondazione Eni Enrico Mattei (FEEM), 2001)
There is a wealth of existing literature on specific methods to encourage public participation in Local Agenda 21. This paper provides a concise overview and comparative assessment of the strengths and weaknesses of these approaches. For the sake of clarity, these methods are categorised into 'traditional' and 'innovative approaches', i.e. those which have been used and tested on a relatively frequent basis and those which are relatively new. Each of these approaches is associated with a number of strengths and weaknesses. Therefore, it is suggested that a combination of methods is adopted in order to reach the wider community, and specific approaches should be selected on the basis of the characteristics of the community in question.
Keywords: I20; J18; 330; Public participation; community participation; Local Agenda 21; Bürgerbeteiligung; Nachhaltige Entwicklung; Welt; Agenda 21